METHOD FOR TREATING ALLERGIC AIRWAYS DISEASE (AAD)/ ASTHMA - SAMUEL, Chrishan; ROYCE, Simon (2024)
The invention relates to use of a mesenchymoangioblast-derived mesenchymal stem cell (MSC-MSC) for treating allergic airway disease (AAD)/asthma in a subject.